Sosialisasi Hukum Waris Pada Masyarakat Kelurahan Wonoplumbon, Kecamatan Mijen, Kota Semarang: Socialization of Inheritance Law to the Community of Wonoplumbon Village, Mijen Subdistrict, Semarang City - Yulies Tiena Masriani; Markus Suryoutomo; Tiara Eldawati (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Inheritance division is a law that regulates the division of property left by someone who has died. This law is to fight for justice for everyone who is entitled to receive inheritance. The law of inheritance division plays a role in regulating how to transfer inheritance from someone who has died to the living, both regarding the inheritance, the people who are entitled to receive, the part that is entitled to be received, and how to settle the division of property. This activity is very necessary for the community, especially for community groups who do not have much access to legal information. This activity is expected to create peace of life and a harmonious family atmosphere. Sharia is the highest source of law that must be obeyed. Sharia itself was revealed for the good of Muslims and provides a solution that best suits the character and character of each human being. Sharia is the highest law that must be obeyed and accepted sincerely.